2003
DOI: 10.1051/0004-6361:20021723
|View full text |Cite
|
Sign up to set email alerts
|

Integrated spectroscopy of bulge globular clusters and fields

Abstract: Abstract. An empirical calibration is presented for the synthetic Lick indices (e.g. Mg 2 , Fe , Hβ, etc.) of Simple Stellar Population (SSP) models that for the first time extends up to solar metallicity. This is accomplished by means of a sample of Milky Way globular clusters (GCs) whose metallicities range from ∼Z /30 to Z ∼ Z , thanks to the inclusion of several metal rich clusters belonging to the Galactic bulge (e.g., NGC 6553 and NGC 6528). This metallicity range approaches the regime that is relevant f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
179
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(190 citation statements)
references
References 82 publications
10
179
0
1
Order By: Relevance
“…11. The models of Maraston (1998) and Maraston et al (2003) are shown as dot-dashed lines, and a few ages of the single stellar population are indicated. EDCSNJ1354025-1232300 z=0.7576 T=3 Fig.…”
Section: Blue-sequence Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…11. The models of Maraston (1998) and Maraston et al (2003) are shown as dot-dashed lines, and a few ages of the single stellar population are indicated. EDCSNJ1354025-1232300 z=0.7576 T=3 Fig.…”
Section: Blue-sequence Galaxiesmentioning
confidence: 99%
“…10 the evolutionary tracks of star clusters in the (U − V, V − J) plane as provided by the models of Maraston (1998) and Maraston et al (2003). We carefully calibrated the zeropoints of these models against the observations of globular clusters of Frogel et al (1980) and Bica & Alloin (1986a).…”
Section: Blue-sequence Galaxiesmentioning
confidence: 99%
“…Hence, this approximation does not account for the temperature and gravity sensitivity of the indices, which causes significant deviations from the giant-turnoffdwarf ratio quoted above. For instance, as shown in Maraston et al (2003), in a 15 Gyr old stellar population with solar metallicity, the dwarfs do contribute 20 per cent to the final Mg index, despite the low continuum flux. This contribution even increases to 60 per cent in the most metal-poor case.…”
Section: Hδa -Ps02mentioning
confidence: 86%
“…A key in the development of these models was the empirical calibration with globular cluster data by Maraston et al (2003). The models have subsequently been updated with new model atmosphere calculations by Korn et al (2005, see also Houdashelt et al2005) for non-solar metallicities and the higher-order Balmer line indices.…”
Section: Brief History Of Element Ratio Modellingmentioning
confidence: 99%